Analysis of the Implementation of Life Skills as an Effort to Enhance Students’ Career Exploration Readiness - Khafidhoh, Inayatul (KONSELING RELIGI, 2025)
This research is motivated by the phenomenon of low career exploration maturity among santri (Islamic boarding school students), which tends to be limited to traditional religious roles. The purpose of this study is to examine the effectiveness of life skill implementation in increasing the career exploration readiness of santri. The method used is a quantitative quasi-experimental approach with a non-equivalent control group design. The research subjects consisted of 60 santri divided into an experimental group and a control group. The data collection instrument utilized the Career Exploration Readiness Scale, which has been tested for validity and reliability. Data analysis was performed using the independent sample t-test. The results showed a significant increase in the average career exploration readiness score in the experimental group after the life skill intervention. The hypothesis test yielded a significance value (2-tailed) of 0.000 < 0.05, indicating that the life skill program effectively improves the students' ability to seek career information, recognize self-potential, and plan for the future. The implications of this study suggest the importance of integrating a life skills curriculum in pesantren to produce graduates who are adaptive to the dynamics of the modern world of work.